Root system architecture for abiotic stress tolerance in potato: Lessons from plants - Zinta, Rasna; Tiwari, Jagesh Kumar; Buckseth, Tanuja; Thakur, Kanika; Goutam, Umesh; Kumar, Devendra; Challam, Clarissa; Bhatia, Nisha; Poonia, Anuj K.; Naik, Sharmistha; Singh, Rajesh K.; Thakur, Ajay K.; et al. (Frontiers in Plant Science, 2022)
Root is an important plant part which uptakes nutrient and water, and provides support to the plant. Abiotic stresses like heat, drought, nutrients, salinity and cold are the major problems of potato cultivation. Significant research advances have been made in cereals and model plants on root system architecture (RSA), and root ideotype (e.g. maize) has been identified for efficient nutrient capture and genes regulating root traits. However, limited work is available on RSA in potato with a few on drought stress and nitrogen use efficiency but meagre on other abiotic stresses. Hence, this mini-review aims to update knowledge and prospects of RSA on abiotic stress tolerance in potato with lessons learnt from model plants, cereals and others.